ANALISA SENSOR SUHU DAN TEKANAN UDARA TERHADAP KETINGGIAN AIR LAUT BERBASIS MIKROKONTROLER - Fitroh Amaluddin; Andy Haryoko (Antivirus : Jurnal Ilmiah Teknik Informatika, 2019)
Tsunamis are natural events that can occur any time without prior warning. Some mitigation efforts both through physical construction consist of sea wave height detection sensors such as DT-Sense Barometric Pressure & Temperature sensors, Infrared sensors, and ultrasonic sensors. However, the sensors have a low accuration and difficult installation. Therefore a device designed to provide temperature and air pressure data based on a microcontroller with higher accuracy, and easier installation. The device are made using a DS18B20 temperature sensor, then air pressure using BMP180 sensor. Sea wave height measurement system based on the working principle of air pressure at sea level. This tool is able to work well at altitudes with a minimum temperature of 25 degrees Celsius. Based on the results of air trials on water levels obtained every 0.1 meter increase in sea air, air pressure increases by 0.02 mb (millibar) or 0.12 mb / meter. While testing the air pressure against the temperature obtained is higher, the air temperature at sea level will increase. Each time the air pressure changes by 1.00 mb, the air temperature at sea level will change an average of around 0.46 degrees Celsius. In other words if the temperature decreases around 1 degree Celsius, then the air pressure also drops by 2.00 mb or around 16.67 meters.